Asthma Control in Canada Remains Suboptimal: The Reality of Asthma Control (TRAC) Study. Issue 5 (2006) - FitzGerald, J Mark; Boulet, Louis-Philippe; McIvor, R Andrew; Zimmerman, Sabrina; Chapman, Kenneth R
Abstract : BACKGROUND: Two Canadian studies showed that 55% of patients with asthma had daily symptoms (in 1996) and that 57% of patients suffered from poorly controlled asthma (in 1999). OBJECTIVES: To assess the state of asthma control of adult Canadians, and asthma knowledge and practices of Canadian physicians actively involved in the care of patients with asthma. METHODS: Telephone interviews were conducted with adults 18 to 54 years of age who had been diagnosed with asthma at least six months before the survey, who did not have chronic obstructive pulmonary disease and who had a smoking history of fewer than 20 pack-years. Physicians were surveyed by telephone and mail. The surveys took place between April and August 2004. RESULTS: Almost all (97%) of the 893 patients believed that they had controlled asthma; however, only 47% had controlled disease according to symptom-based guideline criteria. Just 39% of 463 physicians based their treatment recommendations on the Canadian asthma guidelines most or all of the time, despite having a high awareness of them. Only 11% of patients had written action plans, and one-half of patients with action plans did not use them regularly. Almost three-quarters of patients expressed concerns about taking inhaled corticosteroids. CONCLUSIONS: Since the last major national survey, guideline implementation has not resulted in significant changes in asthma-related morbidity. Effective means of knowledge transfer should be developed and implemented to improve the translation of guideline recommendations into care.